Extended-Spectrum ß-Lactamase-Producing Escherichia coli Among Humans, Beef Cattle, and Abattoir Environments in Nigeria - Aworh, Mabel Kamweli; Ekeng, Eme; Nilsson, Pernille; Egyir, Beverly; Owusu-Nyantakyi, Christian; Hendriksen, Rene S. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction: Beef cattle is linked to humans through a shared environment and the food chain as a major source of animal protein. Antimicrobial drugs are readily accessible for use in livestock production in Nigeria. Beef cattle and abattoir environments harbor pathogenic bacteria which have developed resistance to antimicrobial agents used for prophylaxis or treatment. This study investigated zoonotic transmission of Extended-spectrum Beta-lactamase-producing Escherichia coli (ESBL-EC) among humans, beef cattle, and abattoir environments in Abuja and Lagos, Nigeria. Methods: We conducted a cross-sectional study among abattoir workers, beef cattle, and abattoir environments. Stool, caecal, and environmental samples were collected from July to December 2020. Data were collected electronically using a mobile phone. Phenotypic and genotypic characterization of the isolates was conducted. Data were analyzed with descriptive statistics. Results: Of 448 samples, 21.7% (n=97) were confirmed ESBL-EC by phenotypic characterization. Prevalence of ESBL-EC was highest in cattle (45.4%; n=44), abattoir workers (41.2%; n=40) and abattoir environment (13.4%; n=13). Whole-genome sequencing of ESBL-EC showed dissemination of blaCTX-M-15 (90.7%; n=88); blaCTX-M-14 (5.2%; n=5); blaCTX-M-55 (2.1%; n=2); and blaOXA-1 (1.0%; n=1) genes. The blaCTX-M-15 coexisted with blaCTX-M-14 and blaTEM-1 genes in 2.1% (n=2) and 39.2% (n=38) of the isolates respectively. BlaCTX-M-14 and blaCTX-M-15 genes were significantly associated with isolates from abattoir workers when compared to beef cattle isolates (p=0.05; p<0.01). The prevalent sequence types (ST) were ST10 (n=11), ST215 (n=7), ST4684 (n=7) and ST2178 (n=6). Mcr-1.1 positive ESBL-EC strain (ST205/B1) coexisted with blaCTX-M-15 and was isolated from a worker at Lagos abattoir. In 91 isolates, 219 mobile genetic elements (MGEs) harboured resistance genes out of which β-lactam genes were carried on 64 different MGEs. Isolates showed equal distribution of insertion sequences and miniature inverted repeats although only few composite transposons were detected (humans n=12; cattle n=9; environment n=4). Two isolates from human and cattle (ST46/A) harbouring ESBL genes carried by MGEs were clonally related. Conclusions: First to report blaCTX-M-55 gene in humans and cattle. Horizontal transfer of genes by MGEs was observed. People working closely with cattle or in abattoirs are a high-risk group for faecal carriage of ESBL-EC when compared to the general population.